Organizational culture Mechanisms of formation and dimensions of practice - Sara TALEB; Noureddine AISSANI (Social Sciences Journal, 2019)
Organizational culture plays an essential role in the development of organizations. It represents the organizational origin of the organization through which the events can be expected. The fact that the organization receives human resources loaded with values, beliefs, attitudes and habits formed in their social environment and collides with new values, behaviors. Therefore, the aim of this article is to highlight the importance of building and developing an organizational culture that helps to achieve the best work according to standards and values. The objectives of the organization We will try through this research to identify what the organizational culture and sources of composition and how to form and transfer, learning and distance